Non-typhoidal Salmonella serovars in poultry farms in central Ethiopia: prevalence and antimicrobial resistance - Tadesse Eguale (BMC Veterinary Research, 2018)
Abstract Background Poultry is one of the common sources of non-typhoidal Salmonella and poultry products are the major sources of human infection with non-typhoidal Salmonella. In spite of flourishing poultry industry in the country, data on prevalence and antimicrobial susceptibility of non-typhoidal Salmonella serovars at farm level is not available in Ethiopia. This study investigated prevalence, serotype distribution and antimicrobial resistance of non-typhoidal Salmonella in poultry farms in Addis Ababa and its surrounding districts. Results A total of 549 fresh pool of fecal droppings (n = 3 each) were collected from 48 poultry farms and cultured for Salmonella using standard laboratory technique and serotyped using slide agglutination technique. Susceptibility of Salmonella isolates to18 antimicrobials was tested according to CLSI guideline using Kirby-Bauer disk diffusion assay. Salmonella was recovered in 7 (14.6%) of the farms and 26 (4.7%) of the samples. Salmonella was more common in poultry farms with larger flock size than in the smaller ones and in Ada’a district as compared to other districts. All isolates were obtained from farms containing layers. Two out of 6 (33.3%) farms that kept birds in cage were positive for Salmonella while only 5 (11.9%) of the 42 farms who used floor system were positive. Oxytetracycline was used widely in 40 (83.3%) of the farms, followed by amoxicillin 14 (29.2%) and sulfonamides 11 (22.9%). Salmonella Saintpaul was the dominant serotype detected accounting for 20 (76.9%) of all isolates. Other serovars, such as S. Typhimurium3 (11.5%), S. Kentucky 2 (7.7%) and S. Haifa 1 (3.8%) were also detected. Of all the Salmonella isolates tested, 24 (92.3%) were intermediately or fully resistant to sulfisoxazole and streptomycin, 12 (46.2%) to cephalothin, while 11 (42.3%) were resistant to ampicillin, amoxicillin+clavulanic acid, kanamycin and chloramphenicol. Multidrug resistance (MDR) to several drugs was common in S. Kentucky and S. Saintpaul. Conclusion Despite low prevalence of Salmonella in poultry farms in the study area, circulation of MDR strains in some farms warrant special biosecurity measures to hinder dissemination of these pathogens to other farms and the public. Moreover, awareness creation on prudent use of antimicrobials is recommended.